Exploring the emerging COVID-19 research trends and current status in the field of education: A bibliometric analysis and knowledge mapping - Karakose, Turgut; Demirkol, Murat (My University, 2021)
Background/purpose – The current study aims to analyze the thematic structures and trends of scientific publications that examine the relationship between the COVID-19 pandemic and education, while presenting a roadmap for future research on this topic. Materials/methods – The data were obtained from the Web of Science Core Collection (WoSCC) bibliographic database by identifying the publications that examine the relationship between the COVID-19 pandemic and education, then were analyzed using bibliometric methodology and content analysis. VOSviewer, GraphPad softwares, and visualization maps were used to analyze the data and to present the findings. Results – The results of the study show that publications examining the relationship between the COVID-19 pandemic and education focused on “online education” and “teacher education,” while the countries that contributed the most to publications on this issue were USA, United Kingdom, Canada, and Spain. It was determined that most publications preferred the “theoretical model” and the majority of the research data were obtained through “scale/interview forms.” Furthermore, the findings of this study revealed that during the COVID-19 pandemic period, the editorial/refereeing processes of the articles submitted to academic journals were carried out very quickly and the articles were published unusually quickly. Conclusion – This study indicated that the majority of scientific studies on COVID-19 are focused on the field of health, and that there is limited edition research on COVID-19-related education. To the best of the authors’ knowledge, the current study is the first research article in the international literature to examine the thematic structures and trends of scientific publications on the relationship between solely education and COVID-19 through bibliometric and content analysis; and contributes to the knowledge base on COVID-19-related education by mapping the existing knowledge.
Eğitim alanında ortaya çıkan COVID-19 araştırma eğilimlerini ve mevcut durumu keşfetmek: bibliyometrik bir analiz ve bilgi haritalaması
Makale - Yabancı Dilde Makale
Keywords: COVID-19; Education; Bibliometric analysis; Visualization; Content analysis; Scientometric analysis; Online learning; Online teaching; Distance learning; Coronavirus; Pandemic